Kepuasan Pelanggan pada Westlake Resto: Menggunakan Model Transaksi Spesifik - Yunahar, Rifqi Aulawi; Handayani, Siti Dyah (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to determine the effect of the analysis of food quality, responsiveness, design physic and price to customer satisfaction The Westlake Resto in Yogyakarta.The population of this research is that consumers who ever bought and came to The Westlake Resto in Yogyakarta. The samples in this study of 100 respondens and techniques used are Convenience sampling (sampling by going directly to the place of research). The analysis tool used is multiple linear regression analysis method. This included: validity and reliability test, hypothesis testing through F test and t test and analysis of the coefficient of determinan (R2 ). Based on the analysis conducted found that:Testing the hypothesis by using Test F can be known whether or not a model feasible. Hypothesis testing with t test shows that the four independent variables of food quality (X1), responsiveness (X2), physical design (X3) which proved positively and significantly influence the dependent variable while the price variable (X4) proved negatively and significantly influence the dependent variable customer satisfaction (Y). Adjusted R Square result is 34% customer satisfaction variables able to be explained by four independent variables.